ANALISIS PELAKSANAAN PRAKTIKUM ILMU PENGETAHUAN ALAM (IPA) BIOLOGI KELAS VIII DI SMP NEGERI 3 TAKALAR - Muhammad Riswan Ramli; Yusmar Yusuf; Ningsi Saibi; Nursia Nursia; Aswal Aswal (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
This research is a descriptive study that aims to determine the level of implementation of Science biology lab VIII grade in SMP Negeri 3 Takalar. This sample is a class VIIIA to VIIIB SMP Negeri 3 Takalar taken randomly from each class to achieve the overall sample size of 80 students. Data retrieval is done by using a questionnaire aimed to determine the level of practical implementation, the questionnaire for barriers lab, and the fit between purpose laboratorioum with lab conducted. Data were analyzed using descriptive statistics in the form of percentage and average. Any number of questionnaires were given to respondents were scored practical implementation of the unit so that the percentage of the n obtained from the number of students who answered